Evaluation of Ecosystem Health Based on AWDO-SVR Algorithm in Shiyang River Basin - WANG Wenchuan; LI Lei; ZHENG Ye; XU Dongmei; XU Lei (Renmin Zhujiang)
This paper evaluates the ecological health of Shiyang River Basin by the adaptive wind-driven optimization (AWDO) algorithm and support vector regression (SVR) coupled algorithm for problems in health assessment of watershed ecosystem,finds the optimal parameters of support vector machine (SVM) by AWDO algorithm for uncertainty of parameters from SVM,proposes an evaluation model based on AWDO-SVR algorithm,and evaluates nine indexes such as water resource endowment,water resource development and utilization,and social and economic function of Shiyang River Basin by the model with advantages of fast and simple operation and no need of weight.The results show that the ecological health is sub-health for the upper reaches of Shiyang River,and morbid for the middle and lower reaches respectively.The evaluation result is the same as that of the variable set model,indicating that AWDO-SVR algorithm can be effectively applied to the ecosystem health evaluation of the river basin.